Adsorption Study of Rhodamine B and Methylene Blue Dyes with ZSM-5 Directly Synthesized from Bangka Kaolin without Organic Template - Ani Iryani; Hadi Nur; Mardi Santoso; Djoko Hartanto (Indonesian Journal of Chemistry, 2020)
Rhodamine B (RB) and Methylene Blue (MB) dyes adsorption using adsorbent ZSM-5 synthesized from Bangka kaolin were investigated in this study. The effects of the initial concentration, contact time and temperature on the adsorption process were also analyzed. The effect of the initial concentration and contact time played an important role in the adsorption process; however, the effect differs significantly in both dyes. The temperature plays little role in the dye adsorption process. The results showed the adsorption process occurred in ZSM-5 adhere to Langmuir isothermal adsorption model showing that the adsorption process occurred to be monolayer. Based on the kinetics studies, the pseudo-first-order kinetic model represents the adsorption kinetics that occurs for both dyes onto the synthesized ZSM-5. Thermodynamic parameters namely Gibbs free energy (ΔG°), standard entropy changes (ΔS°) and standard enthalpy (ΔH°) reveal that the adsorption process onto ZSM-5 for both dyes was spontaneous and exothermic.